Gastrointestinal Helminth Infection Improves Insulin Sensitivity, Decreases Systemic Inflammation, and Alters the Composition of Gut Microbiota in Distinct Mouse Models of Type 2 Diabetes - Khudhair, Zainab; Alhallaf, Rafid; Eichenberger, Ramon M.; Whan, Jen; Kupz, Andreas; Field, Matt; Krause, Lutz; Wilson, David T.; Daly, Norelle L.; Giacomin, Paul; Sotillo, Javier; Loukas, Alex (Frontiers in Endocrinology, 2021)
Type 2 diabetes (T2D) is a major health problem and is considered one of the top 10 diseases leading to death globally. T2D has been widely associated with systemic and local inflammatory responses and with alterations in the gut microbiota. Microorganisms, including parasitic worms and gut microbes have exquisitely co-evolved with their hosts to establish an immunological interaction that is essential for the formation and maintenance of a balanced immune system, including suppression of excessive inflammation. Herein we show that both prophylactic and therapeutic infection of mice with the parasitic hookworm-like nematode, Nippostrongylus brasiliensis, significantly reduced fasting blood glucose, oral glucose tolerance and body weight gain in two different diet-induced mouse models of T2D. Helminth infection was associated with elevated type 2 immune responses including increased eosinophil numbers in the mesenteric lymph nodes, liver and adipose tissues, as well as increased expression of IL-4 and alternatively activated macrophage marker genes in adipose tissue, liver and gut. N. brasiliensis infection was also associated with significant compositional changes in the gut microbiota at both the phylum and order levels. Our findings show that N. brasiliensis infection drives changes in local and systemic immune cell populations, and that these changes are associated with a reduction in systemic and local inflammation and compositional changes in the gut microbiota which cumulatively might be responsible for the improved insulin sensitivity observed in infected mice. Our findings indicate that carefully controlled therapeutic hookworm infection in humans could be a novel approach for treating metabolic syndrome and thereby preventing T2D.